Awarded Public Sculptures - Synchronised Swimming, Olympic Building - Antoniou, Klitsa (My University, 2026)
Awarded Public Sculptures - Synchronised Swimming, Olympic Building, Nicosia, Cyprus
Keywords: Arts and entertainment